2021
DOI: 10.51253/pafmj.v71i5.4320
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Torch Pathogens in Congenital Cataract Patients Visiting Armed Forces Institute of Ophthalmology

Abstract: Objective: To assess the rate of positivity of Toxoplasma gondii, Rubella, Cytomegalovirus, Herpes simplex (TORCH) pathogens in patients suffering from congenital cataract in Pakistan. Study Design: Cross sectional comparative study. Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi, from Jun 2017 to Mar 2018. Methodology: Cataract group included sixty children already diagnosed with congenital cataract and control group included 60 children not suffering from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…16 Javaid M et al, in their study reported 21.7% of cases to be positive for Rubella IgG. 23 Puja Dewan in her metaanalysis reported that 10-15 % of CRS cases had Cataract. 24 Recognizing the significant impact of CRS as a preventable cause of morbidity, particularly childhood blindness and deafness with lifelong special health and social needs, WHO has strongly recommended use of rubella-containing vaccines in many countries.…”
Section: Discussionmentioning
confidence: 94%
“…16 Javaid M et al, in their study reported 21.7% of cases to be positive for Rubella IgG. 23 Puja Dewan in her metaanalysis reported that 10-15 % of CRS cases had Cataract. 24 Recognizing the significant impact of CRS as a preventable cause of morbidity, particularly childhood blindness and deafness with lifelong special health and social needs, WHO has strongly recommended use of rubella-containing vaccines in many countries.…”
Section: Discussionmentioning
confidence: 94%
“…The literature are assessed with CASP (Critical Appraisal Skills Program) analisys table and using a modified criteria to assess the literature qualitatively (Table 1). Afterward, the data in literatures are extracted in to the table based on the each ToRCH check up in every literature (Table 2, 3,4,5,6). The data are also extracted based on the ToRCH check up time, which are prenatal, perinatal, and postnatal.…”
Section: Resultsmentioning
confidence: 99%
“…In middle-east asia, there were 60 patient of congenital cataract, 29 of them were positif of Toxoplasma gondii, Rubella virus, Cytomegalovirus, and Herpes Simplex virus with the result of lab test were 35% positive IgG CMV, 21.7% positive Rubella IgG, 13.3% positive Toxoplasma IgG, and 8.3% positive HSV IgG. 3 One of the treatment that can be done is a cataract surgery. However, the cataract surgery is not enough to overcome the congenital cataract.…”
Section: Introductionmentioning
confidence: 99%

The Management of ToRCH Cataract Congenital

Kevin Kekelengenta Ginting,
Wahyuni,
Tri Arif Sampurna
2023
IJRP